FEATURES OF DAILY ECG MONITORING IN PATIENTS WITH PAROXYSMAL ATRIAL FIBRILLATION AND ACCOMPANYING OBESITY - Yuriy Kovbasniuk (Bogomolets National Medical University, 2015)
Summary. Authors examined patients with common heart rhythm disorder - atrial fibrillation and divided them into groups according to BMI. All patients underwent daily Holter ECG monitoring. In all patients with atrial fibrillation the correlation was found between the frequency of atrial ectopia incidence and paroxysms runs and BMI. The obtained data testify the increase of the number and duration of pauses of more than 2 seconds, the decrease in circadian oscillations in heart rate in all patients with atrial fibrillation and the deterioration of all indices with increase of obesity rate. The distinct tendency to the lengthening of the QT-interval was demonstrated both in the group of patients with BMI> 30 kg /m2 and in the group with BMI <23 kg /m2.